Pengembangan Media Pembelajaran KOTASU untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas VI pada Materi Tata Surya - Putri, Yolanda; Saefurohman, Asep; Juhji, Juhji (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
This research addresses the challenge of low critical thinking skills among Grade VI students, particularly in science education, specifically the solar system. The limited availability of suitable learning media exacerbates this issue. The study aims to assess the feasibility and effectiveness of KOTASU-based learning media in improving critical thinking skills in this domain. Employing the Research and Development method, the study garnered favorable evaluations from expert panels, with average scores of 4.4, 4.6, and 4.75 from media, material, and language experts, respectively. Student responses, totaling 93.1% in the